False elevation of cardiac markers: importance of recognition - Yaser Elnahar; Joseph Daoko; Karim El Kersh; et al (Research Reports in Clinical Cardiology, 2011)
Yaser Elnahar, Joseph Daoko, Karim El Kersh, Jennifer C Kam, Chady Sarraf, Fayez ShamoonSt. Michael’s Medical Center, Newark, NJ, USAAbstract: The availability of troponins as cardiac markers in the diagnosis of acute coronary syndrome is invaluable. However, their elevation can sometimes lead the physician astray. We report a rare case of an 86-year-old Hispanic female with a past medical history significant for asthma, hypertension, atrial fibrillation, and dyslipidemia, who presented to the emergency room complaining of a two-day history of shortness of breath associated with wheezing. She denied any chest pain. The patient’s wheezing ameliorated with bronchodilator treatment. However, her admission laboratory investigations were positive for elevated troponin I, with normal creatine kinase (CK) and CK-myoglobin (MB). The first set of cardiac enzymes revealed a troponin I of 29.16 ng/mL (normal < 0.05 ng/mL), CK 234 IU/L, and CK-MB 3.9 IU/L. The electrocardiogram showed rate-controlled atrial fibrillation with nonspecific ST changes. Subsequent cardiac enzymes failed to show any increase in CK or CK-MB. However, the troponin I was, as on admission, persistently elevated at 20.87–29.16 ng/mL. Subsequent cardiac catheterization revealed mild nonobstructive coronary artery disease. Other laboratory tests showed normal creatinine, alkaline phosphatase, and bilirubin, and a negative rheumatoid factor, with absence of hemolysis. A blood sample was subsequently drawn and sent to Beckman Coulter laboratories for heterophile antibody testing. The results confirmed our suspicion of a falsely elevated troponin I caused by the presence of a heterophile antibody. The addition of blocking agents yielded troponin I levels in the normal range. Consistent with current guidelines, we conclude that cardiac markers should be used in conjunction with the clinical picture and the electrocardiogram. This case is unique in that the troponin elevation was incidentally found and led to an array of tests which were all negative.Keywords: troponin I, antibodies, coronary syndrome, electrocardiogram